Nilai Filosofis dalam Karya Sastra Harry Potter - wahyudin wahyu why; Dedi Wahyudi; Aria Septi Anggaira (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2020)
Literature work can influence humans’ character through the thought process of fiction and fantasy world. Essentially, humans have imaginary thoughts which attached to rational, creative and imaginative resilience system. Philosophy values in literature as a determinant of human thought, as a mechanism to function the gap between reality and experiences. This study starts from three important questions: (1) how philosophy values in literature are used in the real life; (2) what factors determine the success of literature works through philosophy values; and (3) how does the use of philosophy values in literature for transforming the life. By using interpretive analysis of observational data and documentation, this study found that: Philosophy values in Harry Potter literature are based on the power of love as a form of philosophy value and become a mechanism for how to interact and to think in life. The success of the philosophy value of the power of love in Harry Potter literature is extracted from cultural traditions, into distinctive characters that are incarnate and function in life. The existence of a Protagonist who upholds the philosophy value of the power of love makes the conflicts that occur can be resolved. The protagonist in this study also has an important position as a central figure which has a relevant function in playing socialization, integration, normative, and social control functions, so that the conflicts in life can be resolved. The use of the concept of literature works in this article succeeds in showing that the philosophy value in the Harry Potter literature in the realm of the power of love is a form of mechanism in the formation of basic traits, personalities, dispositions and characters in life.